Surgical trend and volume effect on the choice of hysterectomy benign gynecologic conditions - Chung- Hong Lin; Cheng- Yu Long; Kuan- Hui Huang; Tsia- Shu Lo; Ming- Ping Wu (Wolters Kluwer Medknow Publications, 2021)
With the advance of minimally invasive surgery (MIS), the surgical trends of hysterectomy changed significantly during past 2 decades. Total number (age-standardized) of all types of hysterectomy decreased, which may be due to the availability of some other alternatives, e.g. hysteroscopy, laparoscopic myomectomy. However, laparoscopic hysterectomy (LH) still remains the mainstream of surgical treatment. LH significantly increases for benign gynecologic conditions in Taiwan and worldwide. The increase of LH was accompanied with decrease of TAH; VH kept stationary, and SAH increased slightly. The increase in popularity of LH and SAH; provides evidence of surgical trends and a paradigm shift for hysterectomy. This time-frame shift suggests LH has reached a u during the later years. Older patients tend to receive AH, while middle-aged women tend to receive LH. Oder surgeons tend to perform AH, while younger surgeons tend to perform LH. However, all type hysterectomy and LH were more commonly performed by older surgeons aged over 50 years. It means both patients and surgeons became older during the time-frames. The above phenomena may also happen due to less young surgeons entered in the gynecologic practice. Most of the LHs were performed by high-volume surgeons, however, there is a shift from high-volume, to medium- and low-volume surgeons. The above scenario may be due to the wide spread of LH techniques. Surgical volume has important impacts on both complications and costs. The high-volume surgeons have lower complications, which result in lower costs. In the future, how to increase the use of LH, to improve the training and monitoring system deserves more attentions.